EFISIENSI TEKNIS DAN PENDAPATAN USAHATANI CABAI MERAH ANGGOTA KOPERASI AGRO SIGER MANDIRI DI KABUPATEN LAMPUNG SELATAN - Tika Leoni Putri; Dyah Aring Hepiana Lestari; Sudarma Widjaya (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze the technical efficiency of red chilli farming, the profitability of red chili farming, and factors that influence the profits of red chili farming and relative economic efficiency. Data collection was carried out in seven sub-districts, namely Sidomulyo, Candipuro, Kalianda, Palas, Penengahan, Ketapang, and Bakauheni of South Lampung District in September 2017 - January 2018. The number of respondents was 41 red chili farmers who were members of the independent Agro Siger Mandiri Cooperative taken by census. Data were analyzed using frontier production functions, income analysis, profit Unit Output Price function, and comparative analysis of relative economic efficiency. The results showed that the red chili farming is veryefficient technically. Red chili farming is beneficial for farmers. The factors influencing the profits of red chili farming are land size, price of pesticides per production, wages of labor per production, and planting groups. Economic efficiency of planting groupone is higher than planting group two.Key words: cooperation, frontier, income, red chilli, technical efficiency